Topics in Fluorescence Spectroscopy Techniques - Lakowicz, Joseph R. (Topics in Fluorescence Spectroscopy, 1999)
In this inaugural volume of a new series, experts in the field help biochemists, analytical chemists, spectroscopists, biophysicists, and other specialists keep up with the latest techniques and technologies available in fluorescence spectroscopy.